SYSTEMATIC LITERATURE REVIEW : KEPUASAN PENGGUNA DAN FAKTOR PENENTUNYA PADA LAYANAN TRANSPORTASI ONLINE DI INDONESIA - Panuntun, Arga Satria; Inayati, Nabilla Rahma; Aprianto, Rizal (Jurnal Qua Teknika, 2025)
Amidst intense competition in the online transportation sector in Indonesia, customer satisfaction has become crucial, yet related research remains fragmented. This study conducted a Systematic Literature Review (SLR) of journals from 2021 to 2025 to map trends, platforms, and factors influencing user satisfaction. The analysis results show that Gojek and Grab are the most frequently studied platforms. Service quality and price are the most commonly analyzed factors and have consistently been proven to have a positive and significant impact on user satisfaction. This study integrates existing findings to provide a comprehensive overview.